2021
DOI: 10.1037/amp0000806
|View full text |Cite
|
Sign up to set email alerts
|

Beyond STEM: The invisible career expectations of Asian American high school students.

Abstract: The overrepresentation of Asian Americans in science, technology, engineering, and math (STEM) occupations can render invisible the early experiences of Asian Americans in other fields. In this study, we provide a national and longitudinal portrait of the occupational expectations of Asian Americans (n = 2,340) in high school and their postsecondary years. Multinomial logistic regression models confirm Asian Americans hold high occupational expectations in STEM fields overall. However, longitudinal results als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Perhaps the most fundamental theme of the special issue centers around the insidious ways in which the model minority myth has shaped the Asian American experience. For example, using a large, nationally representative sample of high school students, Cooc and Kim (2021) empirically demonstrate that Asian American adolescents have far more nuanced career interests, expectations, and paths than might be understood from the model minority stereotype that pigeon-holes Asian Americans as singularly STEM focused. Hwang (2021) also directly interrogates the dangerous role that stereotypes (model minority, in addition to perpetual foreigner objectification and gendered conceptions of beauty) can have on Asian Americans, through mechanisms of internalized oppression that not only devalue the self but also one’s community and coethnics.…”
Section: The First American Psychologist Special Issue Focused On Asi...mentioning
confidence: 99%
“…Perhaps the most fundamental theme of the special issue centers around the insidious ways in which the model minority myth has shaped the Asian American experience. For example, using a large, nationally representative sample of high school students, Cooc and Kim (2021) empirically demonstrate that Asian American adolescents have far more nuanced career interests, expectations, and paths than might be understood from the model minority stereotype that pigeon-holes Asian Americans as singularly STEM focused. Hwang (2021) also directly interrogates the dangerous role that stereotypes (model minority, in addition to perpetual foreigner objectification and gendered conceptions of beauty) can have on Asian Americans, through mechanisms of internalized oppression that not only devalue the self but also one’s community and coethnics.…”
Section: The First American Psychologist Special Issue Focused On Asi...mentioning
confidence: 99%
“…Regarding the focus groups, the community youth workers reported being cognizant of the fact that girls of color can benefit from exposure to STEM enrichment activities that occur outside of school because these non-school activities allow for more "doing" and emphasize creativity and real-world applications in a grade-free environment (Dasgupta & Stout, 2014). Although we found that Asian American girls were especially likely to report being interested in STEM, there is evidence that they too often question their own STEM competence (Cooc & Kim, 2021) and are subject to stereotypical views and attitudes that limit their STEM opportunities (Paik et al, 2018). Thus, these girls should be included in any effort to promote interest and engagement in STEM for girls of color.…”
Section: Discussionmentioning
confidence: 74%
“…While some Asian Americans benefit from selective immigration laws and family resources, many do not. By resisting a focus on model minority stereotypes, psychologists can make visible Asian Americans of differing social classes and employment backgrounds in terms of health (Kim et al, 2021), education (Cooc & Kim, 2021; Luthar et al, 2021), and employment (Tu & Okazaki, 2021).…”
Section: An Asian Americanist Perspectivementioning
confidence: 99%